2013
DOI: 10.3390/g4040561
|View full text |Cite
|
Sign up to set email alerts
|

Population Games, Stable Games, and Passivity

Abstract: The class of "stable games", introduced by Hofbauer and Sandholm in 2009, has the attractive property of admitting global convergence to equilibria under many evolutionary dynamics. We show that stable games can be identified as a special case of the feedback-system-theoretic notion of a "passive" dynamical system. Motivated by this observation, we develop a notion of passivity for evolutionary dynamics that complements the definition of the class of stable games. Since interconnections of passive dynamical sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Hofbauer and Sandholm (2009) developed a method for finding conditions on the payoff function in a class of evolutionary dynamics, called stable or contractive games, that guarantees convergence of strategies to the Nash equilibrium. Fox and Shamma (2013) showed that stable games are “passive” in the sense of feedback systems theory and generalized the method of Hofbauer and Sandholm using the tools of passivity theory (Willems, 1972a; 1972b). The results were further developed in (Park et al, 2019b) and extended to the case in which a networked group of agents experience communication and computational delays in learning the payoffs.…”
Section: Recent Models For Explaining and Shaping Collective Intellig...mentioning
confidence: 99%
“…Hofbauer and Sandholm (2009) developed a method for finding conditions on the payoff function in a class of evolutionary dynamics, called stable or contractive games, that guarantees convergence of strategies to the Nash equilibrium. Fox and Shamma (2013) showed that stable games are “passive” in the sense of feedback systems theory and generalized the method of Hofbauer and Sandholm using the tools of passivity theory (Willems, 1972a; 1972b). The results were further developed in (Park et al, 2019b) and extended to the case in which a networked group of agents experience communication and computational delays in learning the payoffs.…”
Section: Recent Models For Explaining and Shaping Collective Intellig...mentioning
confidence: 99%
“…This model is arguably not very realistic for the routing game, as one does not expect users of a network to have an accurate representation of the cost function on every edge, or of the other users of the network. One alternative model of players is a model of repeated play [25,13,26], sometimes called learning models [11] or adjustment models [15]. In such models, one assumes that each player makes decisions iteratively (instead of playing a one-shot game), and uses the outcome of each iteration to adjust their next decision.…”
Section: Learning Models and Convergence To Nash Equilibriamentioning
confidence: 99%
“…In this sense, players "learn" the equilibrium asymptotically. Much progress has been made in recent years in characterizing classes of learning dynamics which are guaranteed to converge to an equilibrium set [14,18,17,13,26,1]. In particular for the routing game, different models of learning have been studied for example in [12,7,20,22,21], with different convergence guarantees.…”
Section: Learning Models and Convergence To Nash Equilibriamentioning
confidence: 99%
“…Stable games have been studied in the context of transportation science (Dafermos, 1980;Smith, 1979), and more recently in the context of feedback control and passive systems (Fox & Shamma, 2013). Examples of strictly stable games include some types of symmetric normal form games, negative dominant diagonal games, and strictly concave potential games.…”
Section: Population Games and Strictly Stable Gamesmentioning
confidence: 99%